SCENES OF COMMITMENT. (February 2017) - VENKAT, BHARAT JAYRAM
ABSTRACT: What shape does ethical reasoning assume in the face of potentially contradictory commitments? Drawing on fieldwork in a private clinic in Chennai, the capital of the South Indian state of Tamil Nadu, I examine how patients, their families, and the clinic's staff navigated ethically complex situations in which one was called on as both family member and patient. I argue that the doctors and counselors at the clinic attempted to reconfigure the relationship between what were experienced as divergent or contradictory commitments—to treatment and to close kin—in terms of what I call hierarchical subsumption . This mode of response worked not simply to recast treatment as noncontradictory with familial obligations; rather, the commitment to therapy became hierarchically subsumed by and therefore necessary to the fulfillment of such kin‐based commitments. In attending to those ordinary moments in which commitments are felt to be at odds, I suggest that we might develop a better understanding of the particular styles of ethical reasoning that people employ to manage such conflictual situations, which refuse the kind of tacitness that scholars have associated with everyday life.